Micro-abrasion wear behaviour of TiAlCrSiN nanostructured coatings - Martinho, R. P. (2014)
The injection process of glass fibres reinforced plastics promotes the moulds surface degradation by erosion. In order to improve its wear resistance, several kinds of PVD thin hard coatings were used. It is well-known that nanostructures present a better compromise between hardness and toughness. Indeed, when the coating is constituted by a large number of ultra-thin different layers, cracks and interface troubles tend to decrease. However, it is not clear that these nanostructures present a better wear behaviour in erosion processes. In order to study its wear behaviour, a sputtered PVD nanostructured TiAlCrSiN coating was used. The substrate and film surfaces topography were analyzed by profilometry and atomic force microscopy techniques. Film adhesion to the substrate was evaluated by scratch tests. The surface hardness was measured with a Vickers micro-hardness tester. The wear resistance was evaluated by micro-abrasion with a rotating ball tribometer tests. Slurry of SiC particles in distilled water was used in order to provoke the surface abrasion. Different duration tests were performed in order to analyze the wear evolution. After these tests, the wear mechanisms developed were analyzed by scanning electron microscopy. Wear craters were measured and the wear rate was calculated and discussed. With the same purpose, coated inserts were mounted in an injection mould working with a 30% glass fibres reinforced polypropylene. After 45 000 cycles no relevant wear was registered.